2016
DOI: 10.1093/asj/sjw178
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence for Clinical Efficacy of Platelet Rich Plasma in Aesthetic Surgery: A Systematic Review

Abstract: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 82 publications
0
55
0
5
Order By: Relevance
“…However, the final number of platelets in the PRP product is not always proportional to the final number of growth factors, and optimal concentrations are not known . Nonetheless, the lack of scientific rigor in studies evaluating the clinical effects of PRP has not gone unnoticed; some have proposed various classification systems to improve standards for documentation in studies to facilitate comparison of results . Unfortunately, no system incorporates all of the differing properties of PRP and the influence of their emphasized variables on the efficacy of PRP has not been definitively established, which may explain why these systems have yet to be widely adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the final number of platelets in the PRP product is not always proportional to the final number of growth factors, and optimal concentrations are not known . Nonetheless, the lack of scientific rigor in studies evaluating the clinical effects of PRP has not gone unnoticed; some have proposed various classification systems to improve standards for documentation in studies to facilitate comparison of results . Unfortunately, no system incorporates all of the differing properties of PRP and the influence of their emphasized variables on the efficacy of PRP has not been definitively established, which may explain why these systems have yet to be widely adopted.…”
Section: Discussionmentioning
confidence: 99%
“…16 Nonetheless, the lack of scientific rigor in studies evaluating the clinical effects of PRP has not gone unnoticed; some have proposed various classification systems to improve standards for documentation in studies to facilitate comparison of results. 7,[17][18][19] Unfortunately, no system incorporates all of the differing properties of PRP and the influence of their emphasized variables on the efficacy of PRP has not been definitively established, which may explain why these systems have yet to be widely adopted. Once preparation of PRP is perfected and better understood, the potential advantages may justify the growing popularity of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Several preliminary studies have demonstrated that autologous free fat transfer may significantly enhance the healing of pressure sores, critical limb ischaemia, and post‐radiation therapy scars . PRP in isolation has also been shown to have significant regenerative properties . These properties are likely to be due to the release of platelet‐derived mediators such as platelet‐derived growth factor (PDGF), vascular endothelial growth factor (VEGF), transforming growth factor β (TGF‐β), and insulin‐like growth factor (IGF), which promote the recruitment and activation of cells responsible for tissue repair, and they encourage new blood vessel formation.…”
Section: Discussionmentioning
confidence: 99%
“…14 PRP in isolation has also been shown to have significant regenerative properties. [52][53][54][55][56][57] These properties are likely to be due to the release of platelet-derived mediators such as platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), transforming growth factor β (TGF-β), and insulin-like growth factor (IGF), 58,59 which promote the recruitment and activation of cells responsible for tissue repair, and they encourage new blood vessel formation. The addition of PRP to fat grafting has been shown to enhance graft survival through several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet‐rich plasma (PRP) is an autologous blood product containing high concentrations of platelets in a small volume of plasma. Platelets contain hundreds of bioactive molecules in their alpha granules, including growth factors, cytokines, and cell adhesion molecules . The biological rationale for the use of PRP in regenerative medicine involves platelet degranulation, thus allowing for the local delivery of growth factors, modification of the inflammatory response, and stimulation of cell proliferation and differentiation within the target tissue …”
Section: Introductionmentioning
confidence: 99%